Deleuze, Whitehead, Bergson
X, 237 p.
Keywords: This volume explores the relations between the work of Gilles Deleuze, Alfred North Whitehead and Henri Bergson. It examines the articulation between their concepts, methods and modes of philosophy. Themes are examined in the context of the contrasts, differences and conjunctions - the rhizomatic connections - between their shared concepts.